Modeling of Wind Turbines with Doubly Fed Generator System - Fortmann, Jens (Springer, 2015)
Jens Fortmann describes the deduction of models for the grid integration of variable speed wind turbines and the reactive power control design of wind plants. The modeling part is intended as background to understand the theory, capabilities and limitations of the generic doubly fed generator and full converter wind turbine models described in the IEC 61400-27-1 and as 2nd generation WECC models that are used as standard library models of wind turbines for grid simulation software. Focus of the reactive power control part is a deduction of the origin and theory behind the reactive current requirements during faults found in almost all modern grid codes. Based on this analysis, the design of a reactive power control system for wind turbines and wind plants is deduced that can provide static and dynamic capabilities to ensure a stable voltage and reactive power control for future grids without remaining synchronous generation.